1992
DOI: 10.1128/aem.58.5.1727-1739.1992
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of laccase L1 in wood decayed by Rigidoporus lignosus

Abstract: The cellular distribution of laccase Li during degradation of wood chips by Rigidoporus lignosus, a tropical white rot fungus, was investigated by using anti-laccase Li polyclonal antisera in conjunction with immunolabeling techniques. The enzyme was localized in the fungal cytoplasm and was associated with the plasmalemma and the fungal cell wall. An extracellular sheath, often observed around fungal cells, often contained laccase molecules. Diffusion of laccase within apparently unaltered wood was seldom obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 42 publications
(49 reference statements)
1
16
0
Order By: Relevance
“…It has been suggested that early formation of slime layers might facilitate subsequent hyphal penetration of the cell wall (37,50). EFS of R. lignosus were seldom described in vivo during the interaction with rubber tree roots (42, 44) but were commonly observed on wood fragments inoculated in vitro (43). There * Corresponding author.…”
mentioning
confidence: 99%
“…It has been suggested that early formation of slime layers might facilitate subsequent hyphal penetration of the cell wall (37,50). EFS of R. lignosus were seldom described in vivo during the interaction with rubber tree roots (42, 44) but were commonly observed on wood fragments inoculated in vitro (43). There * Corresponding author.…”
mentioning
confidence: 99%
“…Sections were blocked with 0.01 M PBS-1% BSA-0.05% T20 for 10 min, floated on an anti-laccase polyclonal antibody raised against the laccase L1 obtained from Rigidoporus lignosus (Klotsch) Imazeki (Nicole et al 1992) using dilutions between 1 : 800 and 1 : 1200, rinsed in the same buffer and incubated on 0.02 M Tris-HCl-1% BSA-0.05% T20 (pH 8.2) for 10 min before placing the sections on a drop of goat-anti-rabbit-gold (15 nm) for 1 h. Laccases are often reported as oxidative enzymes involved in lignin degradation (Nicole et al 1992). Specificity of the labelling was tested by omitting the primary antibody, by incubating with pre-immune serum or by adsorbing the primary antibody with a commercial laccase (Sigma-Aldrich, Oakville, ON, Canada).…”
Section: Anti-laccasementioning
confidence: 99%
“…We suggest that peroxidases and glucanases first alter the ligno-cellulose complex to facilitate laccase activities. Nicole et al (1992) used the same antibody to localize laccase in wood degraded by the white rot fungus Rigidoporus lignosus (Klotsch) Imazeki. As indicated in their paper, laccase was produced in quantity during wood degradation but, apparently, it was not directly involved in the first steps leading to wood alterations.…”
Section: Anti-b-13-glucansmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular and also extracellular laccase activities remaining associated with cell surfaces have been detected in numerous fungi (Linden et al, 1991;Schlosser et al, 1997;Klonowska et al, 2001and Tetsch et al, 2005, 2006Valaskova & Baldrian, 2006). Extracellular laccase located within extracellular glucan sheaths has been detected in the basiomycete Rigidoporus lignosus (Nicole et al, 1992(Nicole et al, , 1993 and in the ascomycete Botrytis cinerea (Gil-ad et al, 2001). In aquatic fungi, cell-associated laccase activities have not been investigated up to now.…”
Section: Semi-quantitative Reverse Transcriptase (Rt)-pcr Analysis Ofmentioning
confidence: 99%